Delivering Proapoptotic Peptide by HSP Nanocage for Cancer Therapy. Issue 12 (27th May 2020) - Wang, Dongmei; Chen, Li; Wang, Mingyue; Cui, Meiying; Huang, Lili; Xia, Wei; Guan, Xingang
Abstract: Protein nanoparticles have attracted widespread attention in the area of biocatalysis, drug delivery, and vaccine preparation during the past decade. Among various protein nanostructures, protein nanocages have proved to be a multifunctional platform for tumor diagnosis and drug delivery due to easy interior encapsulation and outer surface display. In this report, a protein‐only nanoparticle (HSP‐KLAK) is developed based on small heat shock protein (HSP) nanocage and proapoptotic peptide (KLAK) for enhanced antitumor activity. The HSP‐KLAK nanoparticles show efficient cellular uptake and good lysosomal escape in melanoma cells. Moreover, HSP‐KLAK nanoparticles show significantly enhanced cytotoxicity toward B16F10 melanoma cells compared with free proapoptotic peptide. This study demonstrates that protein nanocage represents an efficient nanocarrier for delivering anticancer peptide into tumors. Abstract : A protein nanoparticle (HSP‐KLAK) based on a small heat shock protein (HSP) nanocage and proapoptotic peptide (KLAK) is reported. The HSP‐KLAK nanoparticles have good cellular uptake and lysosomal escape in melanoma cancer cells. The protein nanoparticles show significantly enhanced cytotoxicity toward B16F10 melanoma cells.